Women and Media: Women's Representation in Job Advertisements - Ningsih, Ayu Setia; Rohmah, Galuh Nur (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
he aesthetic value attached to women and their enigmatic nature represents an intriguing topic for further research. This phenomenon has its roots in a patriarchal cultural system that serves to perpetuate public curiosity regarding women and their representation. In this context, women frequently serve as objects of media representation, engaging in a mutually beneficial symbiotic relationship in which the image of women supports the media's appeal and sustainability. This study employed a qualitative approach utilising the Miles and Huberman interactive model to analyse the representation of women in job advertisements. The data were collected through the social media platform Instagram, with a particular focus on job advertisements in the East Java region. The findings show that the media and women are united in a mutually beneficial relationship, wherein women serve as objects of coverage with the potential to bolster the media's existence. This relationship establishes a balanced dynamic between women and the mass media, reflecting the intricate interplay between cultural norms, societal expectations, and media practices. The implications of this study emphasize the need to critically evaluate media practices that commodify women while considering the broader cultural and societal factors that perpetuate these representations. By shedding light on this dynamic, the research highlights opportunities for media stakeholders to adopt more equitable and empowering portrayals of women in their content.